Tourism and education intersection: cultural reproduction of Osing community in the Angklung Caruk music festival - Karsono Karsono (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2023)
Music festivals are social and cultural events mostly seen as activities to present artistic expressions for the audience to enjoy. If it is investigated closely, the presentation of work at festivals is the final culmination of training and learning, both of which are essential elements of the educational process. This research aims to examine and show that music festivals have educational elements, even in the context of tourism interests. The music festival studied was the Angklung Caruk Festival, a type of traditional music from the Osing community. The festival competes for musical skills between student angklung groups in Banyuwangi, East Java. The research uses ethnographic methods to discover and explain the intersection between festivals' education and tourism dimensions. Data collection uses participant observation techniques, interviews, document study, and documentation. Data analysis uses an ethnographic model, including domain analysis, taxonomy, components, and cultural themes. The research results show that the Angklung Caruk music festival is an arena for competition in the beauty of musical works between student groups to achieve victory. This competition has become a tourism commodity packaged under the title Banyuwangi Festival. To present their best musical works, each angklung group receives intensive and profound education from professional musicians, with the support of the school, government, and parents. Thus, the Angklung Caruk Festival is an arena for reproducing Osing traditional music culture which has an economic and educational dimension. It has an impact on strengthening the identity and social repositioning of the Osing community in the present and future.